Response to “Is CC BY the Best Open Access License?” - Andras Holl (Journal of Librarianship and Scholarly Communication, 2012)
This letter is in response to: Graf, K, Thatcher, S. (2012). Point & Counterpoint: Is CC BY the Best Open Access License?. Journal of Librarianship and Scholarly Communication 1(1):eP1043. http://dx.doi.org/10.7710/2162-3309.1043